Вiдтворення iдiостилю Гiларi Мантел в українськомовних друготворах - Вояківська Аліна (My University, 2023)
Матеріалом наукової розвідки виступає оригінальний текст та український переклад історичного роману «Вулфголл» у виконанні Костянтина Бєляєва та Віталія Михайлюка. Мeтa роботи полягає у виявленні найбільш ефективних методів перекладу характерних рис ідіостилю Г. Мантел. В ході роботи визначено і охарактеризовано жанрову специфіку британського історичного роману. Проаналізовано моделі відтворення типових рис жанру у вітчизняних та закордонних перекладознавчих студіях. Досліджено індивідуальний стиль авторки в змістовному аспекті та особливості відтворення ідіостилю при перекладі роману. Проведено порівняльний лінгвостилістичний аналіз тексту оригіналу роману Гіларі Мантел “Wolf Hall” та його перекладу україською мовою.

The translation of Hilary Mantel’s “Wolf Hall” into Ukrainian by Kostiantyn Bieliaiev and Vitalii Mykhailiuk is a complex process that involves transferring the unique idiostyle of the author while also adapting it to the target culture. The translators successfully managed to reproduce the author's individual style, with its use of archaic language and metaphorical references, while also made adjustments to the text to adapt it for Ukrainian readers. However, the translation also has some shortcomings, such as the excessive use of dialecticisms, which needs additional explanation, as it might sound a bit “foreign” for the vast Ukrainian audience The translation strategies used by Kostiantyn Bieliaiev and Vitalii Mykhailiuk include foreignization, which prevails at all linguistic levels as well as the adjustment of culture-specific elements, the partial use of explanatory notes, and the replacement of the original text with a culturally appropriate equivalent. Overall, the translation can be considered adequate, and it provides Ukrainian readers with an opportunity to experience the boundless literary world of Hilary Mantel.